The effectiveness of 60Co gamma-ray exposure to the reproductive systems of rat (Rattus argentiventer) as sterile male technique - Gusti Ngurah Sutapa; I Wayan Supartha; I NYOMAN WIJAYA; I KETUT PUJA; Mukh Syaifudin (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sutapa GN, Supartha IW, Wijaya IN, Puja IK, Syaifudin M. 2020. The effectiveness of 60Co gamma ray exposure to the reproductive systems of rat (Rattus argentiventer) as sterile male technique. Biodiversitas 21: 3805-3810. Various strategies have been implemented to control pests, however, these do not able to reduce rat attacks on rice plants. Therefore, the sterile male technique (SMT) using 60Co gamma radiation was introduced. A group of rats (Rattus argentiventer) of 2 months age were irradiated with 1-6 Gy doses (dose rate of 99.5631 cGy/min) and the quantity, morphology, and viability of spermatozoa of rats were assessed with standard procedures. The results showed that the concentration of spermatozoa was decreased with increasing radiation doses where for lower than 4 Gy were categorized as normal (>20 million/mL). The morphology of spermatozoa also decreased with increasing radiation dose where under 3 Gy were in normal (> 50%). Spermatozoa viability was also decreased where for doses 1 and 2 Gy were categorized as normal. Statistical analysis showed a significant difference (p<0.05) between the exposed group to control in spermatozoa quantity, morphology, and viability. This finding is quite similar with other experiments on the reproductive appearance of rat based on spermatozoa after irradiation. It is concluded that dose of 3 Gy that caused changes in spermatozoa with its viability still above 50% is the most appropriate dose for SMT of rice field rats.